Do Young Schizophrenics with Recent Onset of Illness Show Evidence of Hypofrontality? - O. Gureje; O. Olley; R. A. Acha; B. O. Osuntokun (Behavioural Neurology)
Young schizophrenic patients (n = 43), manic controls (n = 32), both groups diagnosed according to the Research Diagnostic Criteria and on remission from acute illness, and 53 normal subjects were given a battery of neuropsychologic tests selected to assess different functional areas in the brain. Compared with normal controls, patient groups showed evidence of impaired functioning of many cortical areas but with the schizophrenics having the worst performance. In addition, schizophrenic patients performed poorly in tests designed to assess frontotemporal cortical functioning. This pattern of deficits differentiated schizophrenics from both manic and normal subjects. The results suggest that widespread cognitive deficits are a feature of both schizophrenia and mania but that frontal lobe dysfunction may be more specific to the former. It would also appear that these impairments are not artefacts of age, chronicity or of institutionalization, and are present even in schizophrenic patients who may have an illness with putative better outcome than those studied in previous reports.